Implementasi Manajemen Berbasis Sekolah dalam Meningkatkan Mutu Pendidikan - Hilmaniar, Aulya; Firman, Sufira; Nurhalisa (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2024)
Implementing school-based management (SBM) is an approach to secondary school control that allows schools to autonomously make decisions regarding the planning, implementation and evaluation of academic instruction. In SBM, the principal and all members of the college play an active role in managing assets, developing curriculum and improving the quality of first-grade classes as well as the overall performance of the college. The main goal of comprehensive control at the college level (SBM) is to improve the quality of training uniformly in schools. In order for university management to be applied effectively and efficiently, the important role of the professor as the leader of the college is necessary. It is hoped that the department chair can fulfill his leadership role so that full faculty-based management can be implemented to improve the best quality of education in the school.